IMPLEMENTASI TATA KELOLA PEMERINTAHAN DAERAH BERBASIS DIGITALISASI TEKNOLOGI DI INDONESIA - Riswati Riswati (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2021)
The government is conducting a transformation of Local Governance, based on Digitalization of Technology, for that the author is interested in conducting a research entitled